CASH MANAGEMENT AND ANALYSIS IN THE BANKING SYSTEM - KARPOVA, ANASTASIA; BELOZERTSEV, V.; KHARAKOZ, L. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the economy, there are always agreements on the storage of funds or their redistribution between enterprises and financial institutions. All settlements between enterprises are also conducted with the help of cash. With their help their transformation of a monetary form into production stocks, reception of monetary gain and definition of net income in it comes to the end. Therefore, cash settlements are the most important factor in ensuring the circulation of funds, and their timely completion is a necessary condition for the production process. Most payments between companies are made non-cash, ie by transferring funds from the payer’s account to the counterparty’s account through a system of correspondent accounts between different banks, which can confirm the almost constant relevance of the topic, said that non-cash payments in the current conditions by promissory notes and checks. The articles consider the definition of money prices and their importance in the banking system, as well as the relevance of independent accounts carried out by business entities. The list of available significant tasks of checking cash accounts on bank accounts is given. Problematic aspects of accounting for the movement of monetary services on bank accounts, as well as negative settlements with counterparties are considered. The main problems of development of the banking system of Ukraine at the moment and possible ways to solve them to increase efficiency and stability in the future are considered. The rates of the leading countries with Ukraine were compared and their influence on the banking system was determined.